Facing Students / I Pk-AUD In English Learning For Early Children - Inneh Siera Nainggolan; Elisabeth Situmeang; Ester Viona Sihotang; Djuahadi Silitonga; Mei Lastri Butar-butar (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
Having English language skills is something that many people are very grateful for. including pre-school students who consider themselves to be learning English skills. Many students experience difficulties because their graduate backgrounds are not only from high school, but some are from vocational school. The researcher observed and saw what difficulties pre-school students had in learning English for early childhood. The aim of this research is so that students can develop good strategies in learning English for early childhood.